Niederländische Migranten in Bocholt - Wiesmann, Gerd (Migration nach Bocholt. Zeitzeugen berichten, 2020)
Keywords: Ausländischer Arbeitnehmer; Bocholt; Migration; Niederländer; Soziale Integration

Verre buren. Samenleven in de schaduw van de Holocaust - Demant, Froukje (Ipskamp Drukkers, 2015)
Keywords: Alltag; Grafschaft Bentheim; Hochschulschrift; Interreligiösität; Juden; Judenverfolgung; Münsterland (West); Soziale Integration; Twente

Cross-Border Metropolitan Integration in Europe. The Case of Luxembourg, Basel, and Geneva. - Sohn, Christophe; Reitel, Bernard; Walther, Olivier (Environment and Planning C. Politics and Space, 2009)
Abstract: „In this paper we question the integration processes in three small cross-border metropolitan areas: Luxembourg, Basel, and Geneva. By referring to an original analysis framework, we evaluate the nature and intensity of the functional and institutional integration and highlight the elements that structure the cooperation between the actors. The analysis shows that there is not necessarily a reciprocal link between the size of the functional area and the extent of the cooperation. Whilst no metropolitan-sized organisation is on the agenda in Luxembourg, the example of Basel and Geneva shows that the presence of a national border offers an opportunity to invent original forms of governance, to increase the autonomy of the local authorities by different types of cooperation which transcend the institutional and territorial divides, and to promote the international character of the metropolitan centre. In a context of global competition, these features represent an undeniable benefit.“
Keywords: Basel; Genf; Schweiz; Soziale Integration; Stadt

Métropolisation et intégration transfrontalière. Le paradoxe luxembourgeois - Sohn, Christophe; Walther, Olivier (Espaces et sociétés, 2009)
Abstract: „À partir de l’exemple de Luxembourg, cet article traite de l’intégration des espaces frontaliers métropolitains, en s’interrogeant sur l’articulation de leurs propriétés institutionnelles et fonctionnelles. Dans un premier temps, il questionne l’évolution fonctionnelle de l’aire métropolitaine en prenant pour variable l’intensité des flux pendulaires, l’objectif étant de montrer l’existence d’un espace métropolitain aux dimensions transfrontalières. Dans un second temps, l’article examine les initiatives entreprises dans le domaine de l’intégration institutionnelle par les acteurs politiques. Le cas luxembourgeois permet alors de montrer que, contrairement à d’autres métropoles européennes et de manière paradoxale, il n’existe aujourd’hui aucune gouvernance métropolitaine transfrontalière susceptible de répondre aux enjeux de l’aire fonctionnelle préalablement définie. Cette situation singulière résulte du rôle prépondérant de l’État luxembourgeois – plutôt que de la Ville – dans les dynamiques métropolitaines.“
Keywords: Soziale Integration; Stadt

Zur nationalen Integration fremdnationaler ethnischer Minderheiten und ihren soziopolitischen Konsequenzen, dargestellt am Beispiel der deutschsprachigen gesellschaftlichen Gruppen Eupen-Malmedys zwischen den beiden Weltkriegen. Eine soziologische Untersuchung - Timmermann, Raphael (Aachener Beiträge zur vergleichenden Soziologie und zur China-Forschung, 1989)
Keywords: Eupen-Malmedy; Hochschulschrift; Minderheitensprache; Nationalbewusstsein; Soziale Integration